Efforts to Increase Brand Awareness of Compass Shoes through Digital Marketing Activities - Arief Budiman; Fauziah Yanis (Budapest International Research and Critics Institute-Journal (BIRCI-Journal), 2022)
Digital Marketing activities are a strategy used by the Company to increase sales of the products they make to the public. Moreover, the Digital Marketing strategy used by the brand itself, with the aim of Compass Shoes being one of the local fashion product industries that is able to compete with fashion products in other countries so that Indonesian people know, are proud to use local products and are aware of industrial products fashion shoes. This study suggests aspects of Digital Marketing in building Brand Awareness as an effort to inform, persuade, and remind the Indonesian people about how Compass Shoes market their products ranging from Digital Marketing, Social Media, Messages, Promotional Mix Activities which are used to build Brand Awareness as the goal of study. This study uses a qualitative method that focuses on observation and literature study. Data obtained through observation and interviews and supported by researcher documentation. The informants consisted of two main informants and two additional informants. The results show that Digital Marketing in building Brand Awareness is done by managing the Website, Social Media Instagram and Marketplace which carry out activities in the form of Advertising, Taglines, Running Digital Marketing Techniques such as Social Media, Content Marketing, Social Media Organic, Product Marketing Landing Pages, and Personal Selling, as an effort to build Brand Awareness about Compass Shoes Industry Products.